Administration of Akkermansia muciniphila Ameliorates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice - Bian, Xiaoyuan; Wu, Wenrui; Yang, Liya; Lv, Longxian; Wang, Qing; Li, Yating; Ye, Jianzhong; Fang, Daiqiong; Wu, Jingjing; Jiang, Xianwan; Shi, Ding; Li, Lanjuan (Frontiers in Microbiology, 2019)
Inflammatory bowel diseases (IBDs) develop as a result of complex interactions among genes, innate immunity and environmental factors, which are related to the gut microbiota. Multiple clinical and animal data have shown that Akkermansia muciniphila is associated with a healthy mucosa. However, its precise role in colitis is currently unknown. Our study aimed to determine its protective effects and underlying mechanisms in a dextran sulfate sodium (DSS)-induced colitis mouse model. Twenty-four C57BL/6 male mice were administered A. muciniphila MucT or phosphate-buffered saline (PBS) once daily by oral gavage for 14 days. Colitis was induced by drinking 2% DSS from day 0 to day 6, followed by 2 days of drinking normal water. Mice were weighed daily and then sacrificed on day 8. We found that A. muciniphila improved DSS-induced colitis, which was evidenced by reduced weight loss, colon length shortening and histopathology scores and enhanced barrier function. Serum and tissue levels of inflammatory cytokines and chemokines (TNF-α, IL1α, IL6, IL12A, MIP-1A, G-CSF and KC) decreased as a result of A. muciniphila administration. Analysis of 16S rDNA sequences showed that A. muciniphila induced significant gut microbiota alterations. Furthermore, correlation analysis indicated that pro-inflammatory cytokines and other injury factors were negatively associated with Verrucomicrobia, Akkermansia, Ruminococcaceae and Rikenellaceae, which were prominently abundant in A. muciniphila-treated mice. We confirmed that A. muciniphila treatment could ameliorate mucosal inflammation either via microbe-host interactions, which protect the gut barrier function and reduce the levels of inflammatory cytokines, or by improving the microbial community. Our findings suggest that A. muciniphila may be a potential probiotic agent for ameliorating colitis.